STUDI TINGKAT PARTISIPASI MASYARAKAT KELURAHAN JEMUR WONOSARI DALAM PENGELOLAAN SAMPAH PASCA PROGRAM GREEN AND CLEAN - Amala, Nahawanda Ahsanu; Setyowati, Rr Diah Nugraheni; Oktorina, Sarita (SISTEM Jurnal Ilmu Ilmu Teknik, 2018)
Solid waste problem is happen in many big city, such as Surabaya City. Jemur Wonosari which is participant in Surabaya Green and Clean (SGC) program also have waste management problems. When SGC was conducted, solid waste management is good. However, after the program finished, solid waste management facilities was neglected. In this research we measured solid waste measurement in waste generation and composition from domestic and non-domestic. Also to survey the level of community participation in manage solid waste. The design is quantitative research, data getting from measurement of waste generation and composition also question data to know community participation level in waste management which influenced by internal factors (knowledge, motivation, and environment attitude).The result of research, waste from people in a day is 0,093 kg/person/day. The result of solid waste generation which produced by the community is about 2054,37 kg/day. Waste composition which dominated by food waste, it’s about 43,3%. From the X2 test explain that there is a relation between knowledge, motivation, and environment attitude to community participation and between community participation to solid waste management. The community need to improve composting activities to minimize waste and rise up community participation.